2013
DOI: 10.1186/1129-2377-14-44
|View full text |Cite
|
Sign up to set email alerts
|

Lidocaine injection of pericranial myofascial trigger points in the treatment of frequent episodic tension-type headache

Abstract: BackgroundThe present study aimed to evaluate the efficacy of local lidocaine injections into the myofascial trigger points (TPs) located at the pericranial muscles in patients with episodic tension-type headache (ETTH).MethodsThe study included 108 patients with frequent ETTH that were randomized into 4 groups. One injection of saline (NaCl 0.9%) was administered to group 1 (n = 27), 1 injection of lidocaine (0.5%) was administered to group 2 (n = 27), group 3 (n = 27) received 5 injections of saline (NaCl 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(53 citation statements)
references
References 23 publications
6
45
0
2
Order By: Relevance
“…Venâncio et al found that TrP dry needling was equally effective for decreasing headache and for the use of rescue medication than lidocaine or corticoid injections [49]. These results are similar to those also observed after the application of botulinum toxin A injections over active TrP in individuals with TTH [50,51]. Nevertheless, a recent systematic review concluded that although the literature suggests that TrP dry needling may be a useful addition to conventional physiotherapy in headaches, further research with a stronger methodological design is required [52••].…”
Section: Interventional Studiessupporting
confidence: 63%
“…Venâncio et al found that TrP dry needling was equally effective for decreasing headache and for the use of rescue medication than lidocaine or corticoid injections [49]. These results are similar to those also observed after the application of botulinum toxin A injections over active TrP in individuals with TTH [50,51]. Nevertheless, a recent systematic review concluded that although the literature suggests that TrP dry needling may be a useful addition to conventional physiotherapy in headaches, further research with a stronger methodological design is required [52••].…”
Section: Interventional Studiessupporting
confidence: 63%
“…The efficacy of GON blockade in the treatment of various types of headache has been assessed in a number of studies (9)(10)(11)(12)(13)(14)(15)(16)(17)(18). However, few of these studies were controlled studies.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study has demonstrated that local lidocaine injections into the TrPs could be considered an effective treatment for episodic TTH [98]. Recently, the Special Interest Section of the American Headache Society concluded that TrP injections (trapezius, sternocleidomastoid, and temporalis muscles) with bupivacaine and lidocaine may be effective for the management of TTH: however, evidence-based and standardized treatment protocols are still needed [65].…”
Section: Modulation Trps In Tthmentioning
confidence: 99%